Pengetahuan dan Sikap Remaja Sekaa Teruna Teruni di Daerah Urban dan Sub Urban tentang Perilaku Seksual Berisiko - Abadi, Moh Fairuz; Duarsa, Dyah Pradnyaparamita (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: Sexual risk behaviors  in teenagers, could be a serious  problems in health. Geographical  clould be influence  knowledge and attitudes. Sekaa Teruna Teruni is a Balinese youth organization, they can be  found in all traditional villages.Objective: The research aim’s  to find out the knowledge and attitudes of Sekaa Teruna Teruni in Urban and Sub Urban areas about risky sexual behavior.Methods: This is an cross-sectional study, respondents are 241 teenagers (15-21 years) sampling methode is consecutive, variables were measured  using a questionnaire that had been tested  before, analysis uses non-parametric mann whitney.Results adn Discussion:The results showed  that p score for  knowledge and attitudes <0.05 its means that there are significant.Conclusion: The level of knowledge and attitudes of respondents at the Urban location is higher, that because  the flow of information and the organizational activities, efforts are needed to increase knowledge and attitudes especially at the Sub-Urban. Keywords: Risky sexual behavior; Sekaa Teruna Teruni.